MiR-1224-3p Promotes Breast Cancer Cell Proliferation and Migration through PGM5-Mediated Aerobic Glycolysis. (20th April 2021) - Ran, Fang; Zhang, Yanan; Shi, Yajiao; Liu, Jie; Li, Huayue; Ding, Lihua; Ye, Qinong
Abstract : Metabolic reprogramming of aerobic glycolysis is a hallmark of cancer cells. Regulators of aerobic glycolysis have become targets for cancer diagnosis and therapy. However, the regulators of aerobic glycolysis in breast cancer development have not been well elucidated. Here, we show that the phosphoglucomutase (PGM) family member PGM5 promotes conversion of glucose-1-phosphate (G1P) into glucose-6-phosphate (G6P) and inhibits breast cancer cell proliferation and migration through regulating aerobic glycolysis. In breast cancer patients, PGM5 is significantly downregulated, and its low expression is a predictor of poor prognosis. MicroRNA-1224-3p (miR-1224-3p) inhibits the PGM5 level through directly targeting its 3'-untranslated region and suppresses PGM5-mediated breast cancer cell proliferation, migration, and glycolytic function. Moreover, the miR-1224-3p/PGM5 axis regulates the expression of cell cycle- and apoptosis-related genes and the markers of epithelial-mesenchymal transition (EMT), a process involved in migration and metastasis of cancer cells. Taken together, our results indicate that miR-1224-3p/PGM5 axis plays important roles in breast cancer cell proliferation, migration, and aerobic glycolysis and may be a potential target for breast cancer therapy.